FUNCTIONAL STATE OF THE IMMUNE SYSTEM DURING SPORTS - Masharipova Rano Yusupovna (Modern American Journals, 2025)
In sports today, the increased incidence of illness among athletes and the development of secondary immunodeficiency states due to excessive physical and psycho-emotional stress are pressing issues. Among the numerous studies devoted to this issue, phenomenological studies of changes in the immune system during a single physical activity or a short adaptation period predominate, preventing a thorough understanding of the role and place of the immune system in the structure of adaptive changes in the body during the long-term training of highly qualified athletes. However, effective management of the training process, the safe use of preventive and rehabilitative measures, and immunocorrection agents are only possible based on a thorough, comprehensive understanding of the mechanisms of adaptation and the role of the immune system in this process. Current experimental data indicate the active involvement of the immune system in the development of adaptation syndrome, and that changes in it during physical training can significantly depend on the stage of adaptation. However, these areas of research, while having important theoretical and practical significance, remain underdeveloped. Changes in the immune system under the influence of physical exercise are currently considered primarily within the framework of the classical stress response. According to the tenets of adaptation theory, the stress response, as classically conceptualized, manifests itself only in the initial, imperfect, acute stage of adaptation, which, with repeated implementation, progresses to the next stage—perfect, long-term adaptation or training. Each of these stages accomplishes specific tasks through specific quantitative and qualitative changes in functional systems, among which the immune system occupies a significant place.
Keywords: rehabilitative measures, and immunocorrection agents; effective management